Team foundation server 2008 in action - Azher, Jamil (Manning, 2009)
"Team Foundation Server 2008 in Action is a hands-on guide to Team Foundation Server 2008. Written for developers with a good handle on TFS basics, this book shows you how to solve real-life problems. It's not a repetition of Microsoft's product documentation. Team Foundation Server 2008 in Action is a practitioner's handbook for how to work with TFS under common constraints. This book walks you through real-life software engineering problems based on hundreds of hours of TFS experience." "You'll benefit from expert author Jamil Azher's extensive interactions with members of Microsoft's TFS team and MVPs, survey feedback from the author's blog, and interviews with organizations and user groups using TFS. Instead of just offering a high-level overview, the book provides detailed solutions for solving common - and not-so-common - problems using TFS. It discusses the strengths as well as weaknesses of TFS, and suggests appropriate problem resolution steps, workarounds, or custom solutions."--Jacket